Secondary Metabolites from the Marine Algal-Derived Endophytic Fungi: Chemical Diversity and Biological Activity - Zhang, Peng; Li, Xin; Wang, Bin-Gui (Planta Medica, 2016)
Marine algal-derived endophytic fungi have attracted considerable attention in the most recent two decades due to their prolific production of structurally diverse secondary metabolites with various biological activities. This review summarizes a total of 182 natural products isolated from marine algal-derived endophytic fungi in the past two decades. The emphasis is on the unique chemical diversity of these metabolic products, together with relevant biological activities.
Keywords: seaweed; algal-derived endophytic fungi; secondary metabolites; chemical diversity; biological activity